2017
DOI: 10.1139/cjm-2017-0221
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced stress response of Staphylococcus aureus

Abstract: Transcriptional profiles of 2 unrelated clinical methicillin-resistant Staphylococcus aureus (MRSA) isolates were analyzed following 10% (v/v) ethanol challenge (15 min), which arrested growth but did not reduce viability. Ethanol-induced stress (EIS) resulted in differential gene expression of 1091 genes, 600 common to both strains, of which 291 were upregulated. With the exception of the downregulation of genes involved with osmotic stress functions, EIS resulted in the upregulation of genes that contribute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Strong repression of genes responsible for DNA synthesis and its metabolism was shown in S. aureus exposed to the antimicrobial mupirocin, along with the same for those for translation processes [34]. Similar effects were reported in S. aureus exposed to ethanol, where genes for transcription, translation and nucleotide biosynthesis were generally down-regulated [35]. It has been suggested that exposure to this antimicrobial agent triggers a global adaptation response that is intended to adjust the cell biosynthetic pathways to the availability of energy and the required precursors.…”
Section: Response Mechanisms To Ddac Of the Ddac-adapted S Epidermidsupporting
confidence: 68%
“…Strong repression of genes responsible for DNA synthesis and its metabolism was shown in S. aureus exposed to the antimicrobial mupirocin, along with the same for those for translation processes [34]. Similar effects were reported in S. aureus exposed to ethanol, where genes for transcription, translation and nucleotide biosynthesis were generally down-regulated [35]. It has been suggested that exposure to this antimicrobial agent triggers a global adaptation response that is intended to adjust the cell biosynthetic pathways to the availability of energy and the required precursors.…”
Section: Response Mechanisms To Ddac Of the Ddac-adapted S Epidermidsupporting
confidence: 68%
“…on SOD for tolerance of vancomycin and penicillin is usual for antimicrobial-susceptible enterococci (89). (v) A demonstration of the response to ethanol-induced stress (EIS) in S. aureus strains was provided by the expression of 1,091 genes, of which 291 were upregulated (90). The EIS caused upregulation of genes that promote stress response networks (90), including the ROS response, (p)ppGpp, and TA modules (Fig.…”
Section: Oxidant Tolerance (Ros Response)mentioning
confidence: 99%
“…2). The transcriptional profile of MRSA pathogens indicated that they reacted to EIS by entering a state of dormancy and modifying the expression of elements from cross-protective stress response systems in an effort to preserve the preexisting proteins (90).…”
Section: Oxidant Tolerance (Ros Response)mentioning
confidence: 99%
“…RelP and RelQ share nearly 50% sequence similarity at the amino acid level. relP/relQ genes are upregulated due to various stress cues, such as cell envelope ( Cao et al, 2002 ; D’Elia et al, 2009 ; Geiger et al, 2014 ), alkali ( Nanamiya et al, 2008 ), ethanol ( Pando et al, 2017 ), high salt, acidic, heat, and hydrogen peroxide ( Thackray and Moir, 2003 ; Weinrick et al, 2004 ; Kim et al, 2012 ; Zweers et al, 2012 ). The first SAS proteins (RelP and RelQ) were identified in S. mutans ( Lemos et al, 2004 , 2007 ).…”
Section: Relp and Relqmentioning
confidence: 99%
“…The discovery of SAS and SAH opened a new line of research, to understand the indirect pathways of stress response induced by cues such as cell wall antibiotics, acid, alkali, hydrogen peroxide, ethanol, etc. ( Horsburgh and Moir, 1999 ; Cao et al, 2002 ; Mascher et al, 2003 ; Thackray and Moir, 2003 ; Weinrick et al, 2004 ; D’Elia et al, 2009 ; Kim et al, 2012 ; Geiger et al, 2014 ; Pando et al, 2017 ). We have identified a dual-domain SAS in Mycobacterium smegmatis with RNase HII and (p)ppGpp synthesis activity ( Murdeshwar and Chatterji, 2012 ).…”
Section: Introductionmentioning
confidence: 99%